Comparison the Application of PBL (Project Based Learning) and PBL (Problem Based Learning) Learning Model on Online Marketing Subjects - Agnes Dini Mardani; Titis Shinta Dhewi; Ludiwishnu Wardana (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2017)
Purpose of this study are (1) the application of learning PjBL with PBL to improve study results students, (2) assessing the domain affective, cognitive, and psychomotor, (3) the difference study results use the PjBL with PBL to improve study results students. The research is research quantitative and including research apparent experiment (quasi eksperiment ) by taking sample class two classes X PM 1 as a class experiment and class X PM 2 as a class control. Research instruments used for data collection namely: (1) tests to pretes and postest used to determine the cognitive assessment, (2) sheets observation affective, (3) sheets of the process for the psychomotor. The trial research instruments use the validity and reabilitas. Analysis techniques data using: (1) test a prerequisite analysis consisting of normality test and the homogeneity (2) T test unpaired which ended with the help of computer programs spss. Based on the result of this research can be concluded that: (1) the application of PjBL (Project Based Learning) and PBL (Problem Based Learning) should be conducted well in accordance syntax learning, (2) assessing the cognitive students have a difference and class experiment having an average higher than class control, (3) assessing the results affective students have a difference and on the application of PjBL is better than PBL.